Predicting voltage induced positive-feedback effect on dynamic reset behavior in resistance switching device. (2nd January 2019) - Lin, Chih-Yang; Pan, Chih-Hung; Chen, Po-Hsun; Chang, Ting-Chang; Tsai, Tsung-Ming; Chen, Chun-Kuei; Lin, Yun-Hsuan; Huang, Wei-Chen; Lin, Chun-Chu; Chen, Wen-Chung
Abstract: Investigating dynamic resistance switching behaviors is important for real applications for resistance random access memory (RRAM). In this study, we demonstrate a voltage induced positive-feedback effect which occurs during the reset process under specific conditions, and propose an explanatory mechanism. Since instantaneous change of current always appears with the self-compliance characteristic, research was carried out to clarify the mechanism. We found that the cause is a positive-feedback effect which induces a sudden change in the voltage allocation to the RRAM. A mathematical proof was also carried out to confirm this mechanism, and was used to predict reset behavior when under a specific condition. These experimental and simulation results can help provide a better understanding of the RRAM dynamic reset mechanism.